Strategies for Driving and Creative about Art of Anuban Prachuap Khiri Khan School Under Prachuap Khiri Khan Primary Educational Service Area Office 1 - Kotamalee, Choenjuti; Panich, Anchana (Interdisciplinary Academic and Research Journal, 2023)
The objectives of this research were to study 1) strategies for driving art creative thinking development, 2) strategies for developing art creative thinking of students, and 3) the results of art creative thinking development of students at Anuban Prachuap Khiri Khan School under Prachuap Khiri Khan Primary Educational Service Area Office 1. The action research was used in this study. The samples consisted of 3 art subject network teachers, 40 Prathomsueksa 6 students. The research tools were 1) the manual for developing students’ art creative thinking, and 2) student’s creativity assessment form. Both instruments had the item-objective congruence Index between 0.67-1.00. The data were analyzed by using mean, standard deviation, and percentage of progress. The research revealed that: (1) Strategies for driving art creative thinking development of students were 1) network strategy, 2) communication strategy, 3) participatory strategy, and 4) integration strategy. (2) Strategies for developing art creative thinking of students were creative-based learning management including 5 steps: 1) arouse interest, 2) set problems and divide students into groups according to their interests, 3) research and think, 4) present, and 5) evaluate. (3) The art creative thinking of students after studying was higher than before with a progression percentage of 28.44 %.